Keterkaitan Teori Hegemoni dengan Cerpen â€œPeradilan Rakyatâ€ Karya Putu Wijaya - Umamy, Etty (FKIP Universitas Wisnuwardhana, 2021)
Literary works are created as a means for authors to express their feelings and thoughts and voice their ideas, views, or life hopes. A short story is a form of literary work. Short stories can be dissected with a hegemonic approach. The theory of hegemony is a political theory put forward by Antonio Gramci (1891-1937). The theory of hegemony is suitable to be used to dissect the short story entitled The People's Court by Putu Wijaya. This is because the concept of the story built in the short story of the People's Court refers to the discussion of power. With the hegemonic approach, it is found that there are two models of hegemony that are often used in Putu Wijaya's poem entitled People's Court, namely the concept of coercion and building several forms of hegemony in kinship.